2015
DOI: 10.1007/s13277-015-3770-y
|View full text |Cite
|
Sign up to set email alerts
|

PAQR3 plays a suppressive role in laryngeal squamous cell carcinoma

Abstract: Laryngeal squamous cell carcinoma (LSCC) is a common type of head and neck malignancy worldwide. The molecular mechanism of LSCC remains not well understood. PAQR3 (progestin and AdipoQ receptors) is a member of the progestin and adipoQ receptor (PAQR) family. Many studies have showed that PAQR3 acts as a new tumor suppressor. However, its expression and functions in LSCC are still unknown. In our study, the expression of PAQR3 was downregulated in human LSCC tissues compared to that in adjacent tissues. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…The progestin and adipoQ receptor family, named as PAQR, is a highly conserved protein family that is composed of 11 members, PAQR1 to PAQR11 [ 5 ]. PAQR3 was recently discovered as a new member of tumor suppressor that is deregulated in different types of human cancer including colon cancer, gastric cancer, bladder cancer, liver cancer, osteosarcoma, breast cancer, and laryngeal squamous cell carcinoma [ 6 12 ]. PAQR3, also named as RKTG for Raf kinase trapping to Golgi, is a seven-transmembrane protein that is a type III membrane protein specifically localized in the Golgi apparatus in mammalian cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progestin and adipoQ receptor family, named as PAQR, is a highly conserved protein family that is composed of 11 members, PAQR1 to PAQR11 [ 5 ]. PAQR3 was recently discovered as a new member of tumor suppressor that is deregulated in different types of human cancer including colon cancer, gastric cancer, bladder cancer, liver cancer, osteosarcoma, breast cancer, and laryngeal squamous cell carcinoma [ 6 12 ]. PAQR3, also named as RKTG for Raf kinase trapping to Golgi, is a seven-transmembrane protein that is a type III membrane protein specifically localized in the Golgi apparatus in mammalian cells [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased PAQR3 expression inhibited the growth of ECA-109 cell xenograft tumors ( Zhou et al, 2017 ; Bai et al, 2017 , 2018 ). Compared with adjacent tissues, the expression of PAQR3 in laryngeal squamous cell carcinoma (LSCC) tissues was significantly downregulated, and overexpression of PAQR3 inhibited the proliferation and invasion of LSCC cells ( Wu et al, 2016 ). In osteosarcoma, the expression of PAQR3 was decreased and was associated with metastasis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…PAQR3 overexpression decreased the phosphorylation of ERK1/2 in ESCC cells, without affecting the activation of Akt ( 21 ). PAQR3 has demonstrated the ability to interfere with multiple aspects of tumor biology, including proliferation, migration, invasion, and EMT ( 22 , 23 ). In the present study, it was revealed that the overexpression of PAQR3 suppressed EMT features as demonstrated by the marked increase in the epithelial marker E-cadherin.…”
Section: Discussionmentioning
confidence: 99%